Fulminant Hepatic Failure Caused by Halothane Narcosis - I. G. Khamin; O. I. Andriyanova; Yu. Yu. Merkulov; A. V. Glushkov; A. A. Loktionov; F. K. Manerov (Общая реаниматология)
A case of fulminant hepatic failure (FHF) caused by multiple exposure to halothane hepatitis is described in an 11-year-old child. The major clinical and laboratory symptoms that can optimize the postoperative diagnosis of FHF are depicted. The data available in the literature on the incidence, mechanisms of pathogenesis and outcomes of this anesthetic complication are given.